THE LEARNING OUTCOMES APPROACH IN FORMAL SECOND CHANCE EDUCATION: CASE OF LATVIA - Kuļšs, Dmitrijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper focusses on the use of a learning outcomes approach based on the empirical quantitative data gathered from 82 teachers of the second chance education institutions in Latvia. For this purpose, built on the academic literature and policy documents’ review the author attempts to define the learning outcomes approach. The analysis of the empirical data presents elements of the use of the approach in the setting of a second chance education in Latvia and provides initial findings to support more coherent learning outcome based formal second chance education.